Potential cardiovascular risk reduction with evolocumab in the real world: a simulation in patients with a history of myocardial infarction from the HEYMANS register. (14th October 2021) - Ray, K; Bridges, I; Bruckert, E; Perrone-Filardi, P; Annemans, L; Sibartie, M; Dhalwani, N; Villa, G
Abstract: Background/Introduction: FOURIER included 22, 351 patients with a history of myocardial infarction (MI) and a median low-density lipoprotein cholesterol (LDL-C) of 2.4 mmol/L. Reducing LDL-C with evolocumab reduced the risk of major cardiovascular (CV) events by 1.3%, in absolute terms, over 2.2 years. Whether similar benefits might be observed in real-world evidence from evolocumab use is unknown. Purpose: Simulate CV risk and assess the potential CV risk reduction among a large European cohort of evolocumab users with a history of MI. Methods: We used interim data from HEYMANS, a register of patients initiating evolocumab in routine clinical practice across 12 European countries, from August 2015 with follow-up through July 2020. Demographic and clinical characteristics, lipid-lowering therapy (LLT), and lipid values were collected from routine medical records (6 months prior to evolocumab initiation through 30 months post initiation). Patients with a history of MI were considered and two sub-cohorts were created: recent MI (MI ≤1 year before evolocumab initiation) and remote MI (MI >1 year before evolocumab initiation). For each patient, we 1) simulated their CV risk using three different sources, correcting for age and LDL-C: i) the REACH equation, ii) FOURIER, iii) an observational study including FOURIER-like patients; 2) calculated their absolute LDL-C reduction on evolocumab; 3) simulated their relative risk reduction (RRR) by randomly sampling from the inverse probability distribution of the rate ratio per 1 mmol/L from the key secondary endpoint in the FOURIER landmark analysis; 4) calculated their absolute risk reduction (ARR) and number needed to treat (NNT) over 2 years (recent MI) or 10 years (remote MI). Results: Our analysis included 90 recent MI and 489 remote MI patients initiating evolocumab in clinical practice per local reimbursement criteria, with up to 24 months follow-up. Median (inter-quartile range) age was 59 (53–67) and 61 (53–68) years in recent MI and remote MI patients, respectively. LDL-C before evolocumab was 3.8 (3.2–4.6) and 3.6 (3.0–4.5) mmol/L. Absolute LDL-C reduction on evolocumab was 2.2 (1.4–2.8) and 2.2 (1.6–2.8) mmol/L, meaning relative LDL-C reduction of 60% (44%-73%) and 62% (47%-72%), respectively. Predicted ARR with evolocumab was substantial, whether over 2 years (recent MI) or over 10 years (remote MI). See Table 1. Conclusions: This cohort of evolocumab users in clinical practice had a higher baseline LDL-C and CV risk than patients enrolled in FOURIER. LDL-C reduction and RRR were very similar in recent MI and remote MI patients. However, patients with a recent MI had a higher short-term CV risk and therefore showed a larger ARR on evolocumab. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Amgen